Low-radio frequency observations of seven nearby galaxies with GMRT. Issue 4 (15th September 2021) - Roy, Subhashis; Manna, Souvik
ABSTRACT: We have observed seven nearby large-angular-sized galaxies at 0.33 GHz using Giant Metrewave Radio Telescope with an angular resolution of ∼10 arcsec and sub-mJy sensitivity. Using archival higher frequency data at 1.4 or ∼6 GHz, we have then determined their spatially resolved non-thermal spectrum. As a general trend, we find that the spectral indices are comparatively flat at the galaxy centres and gradually steepen with increasing galactocentric distances. Using archival far-infrared (FIR) MIPS 70-μ m data, we estimate the exponent of radio–FIR correlation. One of the galaxies (NGC 4826) was found to have an exponent of the correlation of ∼1.4. Average exponent from 0.33-GHz data for the rest of the galaxies was 0.63 ± 0.06 and is significantly flatter than the exponent 0.78 ± 0.04 obtained using 1.4-GHz data. This indicates cosmic-ray electron (CRe) propagation to have reduced the correlation between FIR and 0.33-GHz radio. Assuming a model of simple isotropic diffusion of CRe, we find that the scenario can explain the frequency-dependent CRe propagation length-scales for only two galaxies. Invoking streaming instability could, however, explain the results for the majority of the remaining ones.